Digital Learning Product Marketing Strategy in the Marketplace - Yuli Utanto, Maskur Alfaqih, Yoris Adi Maretta (International Journal of Advanced Science and Technology, 2020)
Learning products developed by students majoring in Curriculum and Educational Technology have not been utilized for entrepreneurial capital. Students can take advantage of Ratakan and Idaff marketplace that can be used to sell digital products. They can get grades from the lecturers and also earn a profit. This study aims to analyze the opportunities for entrepreneurship in digital learning products on the marketplace, as well as the utilization of digital learning products for entrepreneurship. The method used is qualitative research. The data analysis technique uses interactive models and data validity techniques using data triangulation. Learning products have the opportunity to be marketed in the marketplace. The use of digital learning products can be marketed in Ratakan and Idaff  marketplace by registering and uploading digital learning products. Digital learning products are used to be distributed to educators to be used in learning activities. Students are able to utilize digital learning products to be disseminated (distribution) in the field of Educational Technology, especially in the dissemination of learning media.Keywords:  learning product, digital learning, marketplace